Forward osmosis–membrane distillation hybrid system for desalination using mixed trivalent draw solution - Nguyen Cong Nguyen (2023)
Finding suitable draw solutions is still a major problem when developing FO technologies. This study represents the first time a mixed trivalent draw solution containing of EDTA–2Na and Na3PO4 was systemically studied for FO performance. The objective here was to achieve simultaneously low reverse salt flux and high water flux. The FO results showed that the mixed trivalent draw solution-based 0.3 M EDTA–2Na and 0.55 M Na3PO4 underwent higher water flux (Jw = 9.17 L/m2⋅h) than that of pure 0.85 M EDTA-2Na (Jw = 7.02 L/m2⋅h) due to its lower viscosity. Additionally, the specific reverse salt flux caused by mixing 0.3 M EDTA–2Na with 0.55 M Na3PO4 draw solution was only 0.053 g/L using DI water as the feed solution. Donnan equilibrium force and formed complexation of [EDTANa]3-, [HPO4Na]- with the FO membrane are believed to constitute the main mechanism for minimizing salt leakage from the mixed draw solution. Moreover, the FO desalination process utilizing the mixed trivalent draw solution achieved water fluxes of 6.12 L/m2⋅h with brackish water (TDS = 5000 mg/L) and 3.10 L/m2⋅h with seawater (TDS = 35,000 mg/L) as the feed solution. Lastly, diluted mixed trivalent draw solution following the FO process was effectively separated using the MD process with salt rejection >99.99% at a mild feed temperature of 55 °C.